THE EFFECT OF APPLICATED ASH SAWDUST ON SWAMP LAND (INDRALAYA) FOR VEGETATIVE GROWTH OF RED PEPPER (Capsicum annum L.) VAR. CEMETI - Pratama, Rahmat; Adriyansah, Fikri; Safitri, Ayu; M.S, Rahman Ismail (BIOVALENTIA: Biological Research Journal, 2017)
The research " The Effect of Applicated Ash Sawdust on Swamp Land (Indralaya) For Vegetative Growth of Red Pepper (Capsicum annum L.) var. Cemeti ’’ has done, from  September to November 2017. It was conducted at green house and Pest Diseases Plant Laboratory, Plant Protection Department, Agriculture Faculty, University of Sriwijaya. This research was aimed to know the effect of applicated ash sawdust on vegetative growth of red pepper. The Completely Randomized Design with treatments are : 10, 20, and 30 g/ kg marshland and without ash sawdust (control), with 6 replicates each treatments. The result showed that applicated ash sawdust on measure 10 g/ kg soil significantly on number of growth 53.28 cm and number of branch 9.2, but not differ on dry weight of red pepper.Keywords :  Swamp land, ash sawdust, branch, red pepper